Leveraging Big Data in The Banking Sector: An Analysis of Challenges and Opportunities at the Central Bank of Aden - Shaima Abdulrahman Mohsen; Dr. Nasr Mohammed Alsakkaf; Prof. Mohammed Fadhl Abdullah; Dr. Ali Saleh Belaeed (مجلة الدراسات الاجتماعية)
Central banks in developing countries face numerous challenges, including counterfeiting and decision-making difficulties. These banks generate vast amounts of data daily, which may not be fully utilized. This study aims to explore the scope, nature, characteristics, sources, and application areas of Big Data in central bank of Aden, with a focus on why central bank should adopt it. The researchers used a descriptive methodology, conducting a comprehensive review of relevant studies, scientific theses, and research papers. The collected data were analyzed using SPSS software. A questionnaire, which was validated by experts and academic staff from the University of Science and Technology, was administered to the information technology management staff at the Central Bank of Yemen's headquarters in Aden and its branches. The study's findings led to several recommendations and identified future research opportunities, emphasizing the study's importance as a foundational effort in this area.